Yodo Rajalangi dan Perkembangan Bahasa Melayu di Tavaeli Palu - Haliadi, Haliadi (KAMBOTI: Jurnal Sosial dan Humaniora, 2020)
The use of the Malay language in Palu Tavaeli introduced by a cleric named Yodo Rajalangi. However, previously there was a cleric named Pue Bulangisi has also introduced Arabic Malay. Both figures come from Mandar scholars. People descent Mandar in Sulawesi Tengah, which introduces the Arabic script for Malay or Malay Language Society Tavaeli Palu in Sulawesi Tengah. Pue Bulangisi become the foundation stone of reading the Qur'an and Arabic Malay in Tavaeli at the King  Daesalemba period (1605-1667). While scholars Yodo Rajalangi is the foundation stone of the use of characters Malay or Language Malay in Palu Sulawesi Tengah at the time of King Yangge Bodu period (1800-1900). However, this article recommends to further research on the beginning of the use of Malay in Sulawesi Tengah.